Engineering design and economic analysis of offshore seaweed farm - Lian, Yushun; Boamah, Samuel Obeng; Pan, Zhenghu; Zheng, Jinhai; Chen, Wenxing; Ma, Gang; Yim, Solomon C. (Frontiers in Marine Science, 2024)
As global demand for sustainable biomass and need to mitigate global warming begin to rise, cultivation of seaweed has gained significant attention in recent years due to its potential for carbon recycling. However, limited availability of suitable coastal areas for large-scale seaweed cultivation has led to exploration of offshore environments as a viable alternative. The nature of many offshore environments often exposes seaweed farming systems to harsh environmental conditions, including strong waves, currents, and wind. These factors can lead to structural failures, kelp losses, and significant financial losses for seaweed farmers. The main objective of this study is to present a robust design and numerical analysis of an economically viable floating offshore kelp farm facility, and evaluate its stability and mooring system performance. A numerical method of preliminary designs of the offshore aquaculture systems were developed using the OrcaFlex software. The models were subjected to a series of dynamic environmental loading scenarios representing extreme events. These simulations aimed to forecast the overall dynamic response of an offshore kelp farm at a depth of 50m and to determine the best possible farm design with structural integrity for a selected offshore environment. Furthermore, to assess the